Pengaruh Ekstrak Etanol Daun Sirih Merah (Piper crocatum) Terhadap Kadar Gula Darah Tikus Putih (Rattus norvegicus) - Sapalma, Krisma Winditia; Ahmad, Tasrif (Universitas Mohammad Husni Thamrin, 2024)
Red betel leaf is a medicinal plant that contains several active ingredients that are beneficial for health. One of the active ingredients in red betelleaves is flavonoids such as quercetin. Quercetin is a flavonoid compound which is found in many plants and has anti-diabetic properties to reduce blood sugar levels in the body. The aim of this research was to determine the effect of administering red betel leaf extract (Piper crocatum) on the blood sugar levels of rats (Rattus novergicus). This research was an analytical experimental research with pretest and posttest. The division of control and treatment groups used Simple Random Sampling sampling techniques. There were 4 groups, namely control, treatment 50 mg/kgBB, 100 mg/kgBB, and 200 mg/kgBB. Treatment was given for 21 days and then blood sugar levels were measured using a Clima MC 15 photometer. Research data was analyzed using the One Way ANOVA Test with SPSS. The results of the Shapiro-Wilk normality test were obtained with a value of sig>0.05; Levene Test homogeneity test with sig. value > 0.05; One Way ANOVA with a sig value <0.05. It can be concluded that there is a real effect on the blood levels of white rats (Rattus norvegicus) after administering ethanol extract of red betel leaves (Piper crocatum) at doses of 50 mg/kgBB, 100 mg/kgBB, and 200 mg/kgBB. kgBB. Key words: Diabetes mellitus, Ethanol Extract of Red Betel Leaves (Piper crocatum), White Rat (Rattus norvegicus)